Service quality offered by Pos Malaysia, Kuala Lumpur in fulfilling customer satisfaction / Norazilah Ramli - Ramli, Norazilah (Faculty of Business and Management, 2006)
This study is about Service Quality Provided by Pos Malaysia in Fulfilling Customer Satisfaction. Service quality is very important in order to produce the best and high quality in product or services in fulfilling customer's needs and wants. Customers are most preferred by the quality rather than quantity. They are willing to pay more to get the best and high quality services. If they satisfied with the services, they will continue using them. If not, they will complaint and maybe stop using the services.